Assessment of Eggshell Quality Before and After Incubation from 29 and 46 Weeks-old Leghorn Hens - Abarca B., Luis D.; Quintana L, Jose A.; Casaubon H., Ma Therese; Rosales, Sergio Gomez (International Journal of Poultry Science, 2011)
Eggshell quality is based mainly upon two important characteristics; its thickness and weight. This study has as an objective to determine the changes in eggshell quality before and after incubation and it consisted of two experiments with 29 and 46 weeks-old leghorn type hens respectively. In both experiments a group was worked upon before incubation (group 1) and another group after incubation (group 2). Experiment 1, group 1 consisted of 40 eggs and group 2 of 100 eggs; both groups had eggs and eggshell without membranes weighed and the percentage was obtained; thickness was measured and the amount of calcium was established. Experiment 2, group 1 had 25 eggs and group 2 had 75 eggs, eggs and eggshell without membranes were weighed and the percentage was obtained, as well as thickness, density and amount of calcium that was present. After that the data were subjected to statistical analysis to establish if the differences were statistically significant. Group 1 had significant differences (p